EDTA-S: A novel root conditioning agent - S Srirangarajan; S Ravindra; S Aparna; S Thakur (Wolters Kluwer Medknow Publications, 2012)
Background: To evaluate the efficacy of 15% ethylenediaminetetraacetic acid (EDTA)-S (EDTA with soft soap) preparation for the removal of smear layer at human root surfaces. Materials and Methods: Twenty teeth indicated for extraction due to periodontal disease were sectioned using high speed cylindrical bur under copious irrigation. The root surfaces were instrumented with Gracey 7-8 curette (Hu-Friedy), 12 times to induce an "experimental smear layer". Following root planning, the root surface was cut using diamond disc and separated from the crown. Samples were randomly distributed into five groups. One group was control, saline and test groups were EDTA 15% alone, by active and passive applications (groups 2 and 3), and EDTA 15%+soft soap, by active and passive applications (groups 4 and 5). Specimens were then subjected to scanning electron microscope study. Smear layer removal was evaluated according to Sampaio et al., index. Results: EDTA-S removed the smear layer better than plain EDTA and the control group, while active application of the root conditioning agent had significant difference than the passive application of the agent. Conclusion: EDTA-S has favorable benefits over EDTA alone, and active application is better in comparison with passive application of root conditioning agent. Clinical Relevance: Removal of smear layer has been considered as an important step in periodontal regenerative therapy. Scaling and root planning alone with saline irrigation does not remove the smear layer. EDTA is a commonly used root conditioning agent in periodontal therapy. The addition of a detergent to EDTA proved to remove smear layer more efficiently than EDTA alone.